Computer and Information Sciences 31st International Symposium, ISCIS 2016, Kraków, Poland, October 27–28, 2016, Proceedings - Czachórski, Tadeusz; Gelenbe, Erol; Grochla, Krzysztof; Lent, Ricardo (Communications in Computer and Information Science,, 2016)
This book constitutes the refereed proceedings of the 31st International Symposium on Computer and Information Sciences, ISCIS 2016, held in Krakow, Poland, in October 2016. The 29 revised full papers presented were carefully reviewed and selected from 65 submissions. The papers are organized in topical sections on smart algorithms; data classification and processing; stochastic modelling; performance evaluation; queuing systems; wireless networks and security; image processing and computer vision.